Peran Suami Disabilitas dalam Menafkahi Keluarga Melalui Tindakan Mengemis: Perspektif Hukum Islam - Adilla, Nurul; Mukhsin, Abd. (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research examines the phenomenon of husbands with disabilities who provide for their families through the act of begging in Sidorejo Hilir Urban Village from the perspective of Islamic law. The main objective of this research is to analyze the practice of husbands with disabilities fulfilling financial support obligations and to explore the local community’s views on this phenomenon. This research uses a juridical-empirical approach with a qualitative method. Primary data were obtained through in-depth interviews with four husbands with disabilities and several residents and community leaders. Secondary data were collected from a literature study of Islamic legal sources, such as the Qur’an, Hadith, and books of fiqh (Islamic jurisprudence). The results showed that physical limitations and barriers to access to decent work forced husbands with disabilities to beg in order to fulfil their family financial support obligations. From Islamic law’s perspective, begging can be justified due to the condition of dharuriyyat (necessity), although this permissibility is temporary and situational. The Sidorejo Hilir Urban Village community shows various views, ranging from empathy and tolerance to criticism that emphasizes the importance of independence. This research concludes that the condition of dharuriyyat justifies begging as an exception to the general rule while still prioritizing the principle of izzah (self-dignity). The implication of this research is the need for strategic steps, especially from the government and related institutions, to create inclusive economic empowerment programs for persons with disabilities so that they can escape the condition of dharuriyyat and fulfil their financial support obligations more dignifiedly.